2021
DOI: 10.5334/bc.120
|View full text |Cite
|
Sign up to set email alerts
|

Windows: a study of residents’ perceptions and uses in Sweden

Abstract: What are inhabitants' perceptions and uses of windows in multi-dwelling buildings? This paper reports on a field study that explores daylight, the visual connection to the outside and the role of windows in the home during the day and night. Qualitative interviews were held with 20 participants living in multi-dwelling buildings. The thematic analysis identified two main components as characteristic of residents' experiences with their windows. The first, 'perceived dwelling comfort', consists of different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Journal of Sustainable Architecture and Civil Engineering 2024/2/35 60 experiences of comfort, for example, brightness, indoor appeal, improved mood, spaciousness and visual privacy, to mediate information about outdoor conditions and the interaction between residents and people outside-allowing observation, verbal communication and the use of intentional or unintentional visual cues (Gerhardsson et al, 2021). The weighted average thermal transmittance of existing windows with two glass panes is quite high (U≈2.2 W/(m²•K)) containing high potential for decreasing thermal transmittance while it is more than three times lower for modern triple glazing (U≈0.6 W/(m²•K)).…”
Section: Windowsmentioning
confidence: 99%
“…Journal of Sustainable Architecture and Civil Engineering 2024/2/35 60 experiences of comfort, for example, brightness, indoor appeal, improved mood, spaciousness and visual privacy, to mediate information about outdoor conditions and the interaction between residents and people outside-allowing observation, verbal communication and the use of intentional or unintentional visual cues (Gerhardsson et al, 2021). The weighted average thermal transmittance of existing windows with two glass panes is quite high (U≈2.2 W/(m²•K)) containing high potential for decreasing thermal transmittance while it is more than three times lower for modern triple glazing (U≈0.6 W/(m²•K)).…”
Section: Windowsmentioning
confidence: 99%
“…Window views are physically and psychologically beneficial to building occupants and can effectively reduce discomfort, according to a field study in the Netherlands [76]. Further research revealed that openable windows provide sufficient indoor space and allow exposure to external elements (e.g., air, sound, light, people outside), and allow the expression of personal control [77].…”
Section: Opening Windowsmentioning
confidence: 99%
“…The primary motivation for adding participant photography to the research method was the expectation of obtaining more information. Findings in recent literature show that adding participant-produced photographs or videos to the research studies has multiple benefits in knowledge production, from both the researcher and participant perspectives [37][38][39]. The photos may considerably enrich the data by showing details and features of the environment that otherwise have to be omitted as the length of the survey has to be restricted to avoid bothering participants too much, and to avoid participation rejection.…”
Section: Survey Descriptionmentioning
confidence: 99%